Role conflicts of management accountants and their position within organisation structures - Hopper, Trevor M. (Accounting, Organizations and Society, 1980)
The research examines accountants' and managers' perceptions of management accounting roles under conditions of centralisation and decentralisation of the management accounting function. Decentralization was associated with greater interaction between accountants and other managers and with the provision of accounting information perceived as being more pertinent to managerial needs. However, whatever the structural relationship, there were criticisms of the accountants' passivity in management. Contrary to expectations neither interpersonal relationships nor excessive power of accountants were problematical, nor did many accountants show bureaucratic orientations. Their inability to meet service expectations were perhaps, related to ambiguity and stress emanating from the accounting workflows.